Does the Interval Slide Procedure Reduce Supraspinatus Tendon Repair Tension?: A Biomechanical Cadaveric Study. Issue 1 (11th January 2022) - Porschke, Felix; Nolte, Philip Christian; Knye, Christian; Weiss, Christel; Studier-Fischer, Stefan; Gruetzner, Paul Alfred; Guehring, Thorsten; Schnetzke, Marc
Background: The benefits of the interval slide (IS) procedure in retracted rotator cuff tears remain controversial. Purpose: The purpose was to evaluate the effect of the IS procedure on repair tension (RT). It was hypothesized that the IS procedure (anterior IS [AIS], posterior IS [PIS], and intra-articular capsular release [CR]) would reduce the RT of a supraspinatus tendon. Study Design: Controlled laboratory study. Methods: A total of 31 Thiel-embalmed human cadaveric shoulders (mean age, 74 years; range, 68-84 years) were tested. Full-thickness supraspinatus tendon tears were created, and 1 cm of tendon was resected to simulate a retracted defect. Shoulders were randomized into intervention (n = 16) and control (n = 15) groups. In all shoulders, the load during tendon reduction to footprint was measured, an endpoint was defined as maximum tendon lateralization before 50 N was reached, and the RT (load during lateralization to endpoint) of the native tendon (t1 ) was evaluated. In the intervention group, AIS (t2 ), PIS (t3 ), and CR (t4 ) were performed in order, with RT measurement after each step. In the control group, RT was assessed at the same time points without the intervention. Results: A complete reduction of the tendon was not achieved in any of the shoulders. Mean maximum lateralization was 6.7 ± 1.30 mm, with no significant differences between groups. In the intervention group, the overall IS procedure reduced RT about 47.0% (t1 vs t4 : 38.7 ± 3.9 vs 20.5 ± 12.3 N; P < .001). AIS reduced RT significantly (t1 vs t2 : 38.7 ± 3.9 vs 27.4 ± 10.5 N; P < .001), whereas subsequent PIS (t2 vs t3 : 27.4 ± 10.5 vs 23.2 ± 12.4 N; P = .27) and CR (t3 vs t4 : 23.2 ± 12.4 vs 20.5 ± 12.3 N; P = .655) did not additionally reduce tension. Comparison between groups at t4 revealed a reduction of RT of about 47.8% (control vs intervention: 39.3 ± 4.0 vs 20.5 ± 12.3 N; P < .001). Conclusion: The IS procedure reduces RT of the supraspinatus tendon in human cadaveric shoulders. However, performing PIS and CR subsequent to AIS does not reduce tension additionally. Clinical Relevance: These findings provide surgeons with a biomechanical rationale regarding the efficacy of the IS procedure.